CATFISHING DALAM PERSPEKTIF HUKUM POSITIF INDONESIA - Atika Zahra Nirmala; Ayu Riska Amalia; Nunung Rahmania; Zahratul’ain Taufik (IAIN Padangsidimpuan, 2023)
This study aims to analyze catfishing in the perspective of Indonesian positive law. This research is a type of normative juridical research with statutory and case approach methods and then uses descriptive qualitative analysis techniques. The results of this study indicate that catfishing is one of the crimes that use technology by utilizing social media where catfishing which is a form of fraud in cyberspace with its modus operandi using a fake identity then showing interest in other people so as to form an emotional or romantic relationship, and then using the victim to benefit himself by giving something in the form of goods or money. Therefore, based on Indonesian positive law the act above is a crime which fulfills the elements in Article 378 of the Criminal Code and Article 35 in conjunction with Article 51 paragraph (1) of the ITE Law. With the existence of these rules can accommodate the crime of catfishing and the catfish although there is no cyberlaw that specifically regulates crimes such as catfishing.